Climate impact on typhoid disease in Iraq for the period (1990-2019) (Journal of the College of Basic Education, 2022)
The climate with its basic elements (solar radiation, temperature, wind, weather humidity and rain) is the most important among the components of the natural environment in which a person lives, because of its effective impact on human comfort and health, its various activities and its affliction with endemic diseases through its direct impact on pathogens and vectors of insects and the proliferation of parasites Germs and viruses and in the multiplication of disease-transmitting or reservoir organisms for their microbes, as these favorable climatic elements provide ideal conditions for pathogens, especially typhoid disease.Through the study, it appeared that typhoid disease could appear in the central and southern regions of the study area as a result of the spread of swamps, marshes and stagnant water. The study also showed that typhoid disease could appear in mountainous and semi-mountainous areas, which was characterized by a high incidence of the disease, in order to adapt some of the deportations of this environment, especially Nineveh and Kirkuk governorate .tor analysis demonstrated that the strongest variables influencing typhoid disease are x4 (maximum temperature), followed by (x2 the normal temperature), followed by (x3 minimum temperature) followed by (x5 wind), followed by (x1 solar brightness) and then in the opposite direction of the two variables (x7 rains), Then (relative humidity x6).